The Impact of Micromanaging by Zoomer Generation on Baby Boomer: Effect on Physical and Mental Health at PT XYZ - Dodi Putra Purnama; Mujiono Pangestu Alam; Siti Mujanah; Achma Yanu Alif Fianto (LPPM STIE Kasih Bangsa, 2025)
This study examines the impact of micromanagement practices by Generation Z (Zoomers) on employees from the Baby Boomer generation at PT XYZ, a company specializing in maritime shipping services. The research focuses on the responses of Baby Boomer employees, particularly in relation to their physical and mental well-being. Data for the study were gathered through surveys and interviews involving employees from both generational cohorts. The findings indicate that micromanagement practices implemented by Zoomers can significantly contribute to physical and mental health challenges among Baby Boomer employees